Digital Archaeology: From Interdisciplinarity to the ‘Fusion’ of Core Competences - Moscati, Paola (magazén, 2021)
The aim of this article is to explore the interdisciplinary turn observed in the development of humanities computing, in terms of integration and fusion of expertise. The debate started with the Seminar on Discipline umanistiche e informatica. Il problema dell’integrazione, held in 1991 at the Accademia Nazionale dei Lincei. Moving backwards in time, already from the 1960s the role of ‘integration’ was at the heart of many interdisciplinary initiatives supported by the National Research Council of Italy and the Accademia Nazionale dei Lincei as part of their coordinated efforts to promote scientific progress. Through a number of archaeological case studies pivoting around the Etruscan civilisation, it will be shown how over time archaeological computing, and its evolution towards digital archaeology, has found in GIS and multimedia systems a unitary platform on which methods and practice of data acquisition, analysis, interpretation, and communication can converge. The concept of ‘fusion’, however, is much more recent and responds to a global resource management model, which combines the methods of archaeology with the objectives of Heritage Science, along the research path that goes from field and laboratory investigation to the protection, enhancement and communication of cultural heritage.